Jaringan Kebijakan Publik, Implementasi Kebijakan Syari'at Islam Di Kabupaten Bireuen, Provinsi Aceh - Taufik Taufik (Jurnal Transformasi Administrasi, 2016)
Aqidah silting in policy implementation Shari'a is a complex problem, so it needs a networkbased organization solution. The aim of the research was to describe the regulative, normative and cognitive pillars in the network of Islam Syari'ah policy implementation in Bireuen, Aceh Province. The research approach was qualitative. Data were collected with observation, interview, and documentation study, and analyzed with reduction, presentation and conclusions/verification. The results of the research indicated that (1) the regulatory pillar does not operate effectively, in the absence of sanction given to the offender, and also the absence of special rules made by TPWNAAS in their duties, which includes regulations, laws, sanctions and competence in carrying out policy implementation of Syari'ah in Bireuen. (2) normative pillar has not been fully effective, because of shortage of competent human resources in the Departement of Islamic Syari'ah as a member of TPWNAAS, and some staff with unsuitable educational background. (3) cognitive pillar has been running effectivelly, indicated by believes, goals, and actions jointly undertaken by institutions were incorporated in TPWNAAS and a shared vision and mission, as well as mutually agreed objectives in implementing the policy of Islamic Syari'ah in Bireuen.